2006
DOI: 10.1111/j.1445-5994.2006.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and validation of three measures of quality of life in patients with pulmonary hypertension

Abstract: The MLwHF questionnaire and SF-36 are useful tools for the assessment of QoL in pulmonary hypertension and may be useful in the ongoing evaluation of QoL in the treatment and study of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 23 publications
0
62
0
10
Order By: Relevance
“…On the other hand, hemodynamics had no association with either the physical or mental component scores (discriminant validity). Investigators have shown similar correlations between the physical subscore of the modified MLHF questionnaire with functional class, 6MWD, RA pressure and CI [87,107]. The MLHF score was also associated with event-free survival [107].…”
Section: Quality Of Life (Qol)mentioning
confidence: 72%
See 3 more Smart Citations
“…On the other hand, hemodynamics had no association with either the physical or mental component scores (discriminant validity). Investigators have shown similar correlations between the physical subscore of the modified MLHF questionnaire with functional class, 6MWD, RA pressure and CI [87,107]. The MLHF score was also associated with event-free survival [107].…”
Section: Quality Of Life (Qol)mentioning
confidence: 72%
“…A recent report substantiated the impact of changes in 6MWD on health status and QOL [87]. However, 6MWD may also be linked to survival in PAH, making it a surrogate end point as well.…”
Section: Exercise Testing Six Minute Walk Test (6mwt)mentioning
confidence: 99%
See 2 more Smart Citations
“…It also correlates with New York Heart Association Functional Class [127] and quality of life [129]. Similarly change in six minute walk distance (Δ6MWD) following PAH treatment correlated with changes in cardiac index, PVR [130] and quality of life [129].…”
Section: Field Exercise Testsmentioning
confidence: 97%